RANCANG BANGUN SMART CRYSTALLIZER BERBASIS IOT UNTUK OPTIMALISASI PRODUKSI GARAM DI ERA INDUSTRI 4.0 - Syaifuddin Syaifuddin; Taufiq Ramdani (LPPM Institut Pendidikan Nusantara Global, 2025)
Small-scale salt production in Indonesia still faces classic problems such as dependence on weather, low productivity, and inconsistent quality. This situation has a direct impact on the low competitiveness and unstable income of salt farmers. This programme aims to empower the salt farming community in Pamekasan District, Madura, through the implementation of an Internet of Things (IoT)-based Smart Crystalliser designed to monitor environmental parameters in real time, so that the crystallisation process can be controlled more efficiently and adaptively. The method used is community-based participatory research (CBPR), which emphasises active community involvement from the planning, testing, training, to evaluation stages. Implementation testing was carried out at the Pamekasan community salt ponds, while academic validation was conducted through the 2025 Science, Technology and Industry Convention (KSTI) at the Bandung Institute of Technology. Data was collected through participatory observation, interviews, questionnaires, and technical prototype testing. Analysis was conducted quantitatively using the paired sample t-test and qualitatively using the Miles & Huberman model. The results of the activity showed an increase in salt productivity of ±20%, an acceleration in crystallisation time of up to 25%, and an improvement in salt quality with an NaCl content of ≥97%. Community participation was quite high, with more than 70% of farmers able to operate the monitoring application independently. This programme has had a tangible impact in the form of a 15–20% increase in farmers' income while strengthening the community's independence in managing salt ponds. Thus, the application of the IoT-based Smart Crystallizer has proven to be effective as an appropriate technological innovation that meets the needs of traditional salt farmers. This programme contributes to the independence of the national salt industry in the Industry 4.0 era and opens up opportunities for replication in other salt centres in Indonesia.